2021
DOI: 10.1038/s41598-021-92459-7
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnan sulphate from green algae Monostroma nitidum improves constipation with gut microbiome alteration in double-blind placebo-controlled trial

Abstract: Rhamnan sulphate (RS), a sulphated polysaccharide from Monostroma nitidum, possesses several biological properties that help in treating diseases such as viral infection, thrombosis, and obesity. In the present study, we first administered RS (0.25 mg/g food volume) orally to high-fat diet-treated mice for 4 weeks. RS increased the faecal volume and calorie excretion with decreased plasma lipids, which was in accordance with the results of our previous zebrafish study. Notably, as the excretion amount by RS in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 53 publications
(49 reference statements)
2
17
1
Order By: Relevance
“…They showed an increase in the total gastrointestinal (GI) transit time and colon transit time and a decrease in the amount of colonic mucus [ 8 ]. A similar decrease in the fecal amount was observed in the NSY/HOS mice fed a HFD for four weeks [ 9 ]. On the other hand, the level of fecal mucin was maintained in the SD rats treated with a low-fat diet (LFD) and HFD for three weeks [ 10 ].…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…They showed an increase in the total gastrointestinal (GI) transit time and colon transit time and a decrease in the amount of colonic mucus [ 8 ]. A similar decrease in the fecal amount was observed in the NSY/HOS mice fed a HFD for four weeks [ 9 ]. On the other hand, the level of fecal mucin was maintained in the SD rats treated with a low-fat diet (LFD) and HFD for three weeks [ 10 ].…”
Section: Introductionsupporting
confidence: 67%
“…In particular, significant changes in the constipation parameters were detected in the HFD-induced obesity model. The fecal weight and calories were lower in the NSY/HOS mice with obesity induced by four weeks of HFD, while the decrease in stool parameters, increase in GI transit time, and decrease in the colonic mucus level were observed in the C57BL/6 mice treated with a HFD for eight weeks [ 8 , 9 ]. The number of nNOS myenteric neurons and enterochromaffin (EC) cells and the 5-HT concentration were lower in the Western diet (WD)-treated C57BL/6 mice and rats [ 7 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…All fermentable DF is consumed as food moves toward the distal colon, and stool mass and water content with regard to reducing colon transit time are determined by insoluble, poorly fermented DF ( 31 ). It is generally believed that constipation can lead to complications such as fecal impaction, bowel perforation, and hemorrhoids, accompanied by inflammation in the gut mucosa ( 43 , 44 ). Likewise, a previous study also indicates that mothers were found to have symptoms of metabolic syndrome during late gestation and lactation, mainly characterized by low-level inflammation and metabolic disorder ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…75 Extensive literature suggests that RS plays an important role in preventing obesity and treating obesity-related metabolic diseases. 63,76–79 The oral administration of RS can decrease body weight gain, hyperglycemia, dyslipidaemia (TC, TG and LDL-C), insulin resistance and hepatic steatosis in diet-induced obesity (Table 5). 80 Specifically, treatment with RS is beneficial for keeping the ratio of LDL/HDL cholesterol at a low level, which can inhibit the overgrowth and differentiation of adipocytes and alleviate the inflammatory infiltration.…”
Section: Green Algaementioning
confidence: 99%
“…For example, it reduces the number of Firmicutes while increasing the number of Bacteroides. 76 Firmicutes / Bacteroidetes ratio is significantly associated with BMI, and reduction of Bacteroidetes can suppress obesity. 81…”
Section: Green Algaementioning
confidence: 99%